Hubungan Antara Dukungan Sosial dengan Kesehatan Mental Pada Remaja - Vallahatullah Missasi (Pelantar Press, 2026)
Late adolescence is a transitional phase toward early adulthood. College students face various academic, social, and personal demands that can potentially impact mental health. Social support is viewed as a protective factor that plays a crucial role in maintaining an individual's psychological well-being. This study aims to determine the relationship between social support and mental health in late adolescent college students. The research method used was a quantitative approach with a correlational design. The subjects consisted of 120 college students aged 18–24 years old selected using a purposive sampling technique. The research instruments included the Multidimensional Scale of Perceived Social Support (MSPSS) and the General Health Questionnaire-12 (GHQ-12). Data analysis was performed using Pearson Product Moment correlation. The results showed a significant positive relationship between social support and college students' mental health (r = 0.47; p 0.01). This finding indicates that the higher the social support received by college students, the better their mental health. This study emphasizes the importance of the social environment in supporting college students' mental health during late adolescence